Strategic Selection of Telecom Operators to Counter OTT - Min Zhang; Jie Song; Xiaofeng Liu (Dianxin kexue)
The influence which OTT brings to carriers was analyzed，the differences between OTT and telecom operators were compared，and the strategic selection for the domestic telecom operators was proposed by domestic and foreign telecom operators case study.